Coordinating a Multi-Platform Disinformation Campaign: Internet Research Agency Activity on Three U.S. Social Media Platforms, 2015 to 2017. (3rd March 2020) - Lukito, Josephine
Abstract : Though nation-states have long utilized disinformation to influence foreign audiences, Russia's 2015 to 2017 campaign against the U.S.—executed by the Internet Research Agency (IRA) —is unique in its complexity and distribution through the digital communication ecology. The following study explores IRA activity on three social media platforms, Facebook, Twitter, and Reddit, to understand how activities on these sites were temporally coordinated. Using a VAR analysis with Granger Causality tests, results show that IRA Reddit activity granger caused IRA Twitter activity within a one-week lag. One explanation may be that the Internet Research Agency is trial ballooning on one platform (i.e., Reddit) to figure out which messages are optimal to distribute on other social media (i.e., Twitter).